Quelques remarques sur la notion de médiation en traduction - Szeflińska-Baran, Magdalena (Studia Romanica Posnaniensia, 2024)
The socio-cultural role of translators is undergoing rapid changes in the lives of societies affected by globalization. The objective of the article can be summed up in questioning the traditional role of the translator consisting, among other things, in what Jean Peeters (1999) calls “the mediation of the foreigner”. The question that arises, therefore, concerns the possibility of existence of the strangeness and relevance of this notion in the globalized world. The process of unifying a global market for cultural, symbolic and literary goods calls into question the need for mediation at the level of languages and cultures. The aim of the article is therefore to analyze from the sociolinguistic perspective new sociocultural roles that could assume the translator in the face of the unification process.